Efficiency-aware nonlinear model-predictive control with real-time iteration scheme for wave energy converters - Guerrero-Fernandez, Juan L.; González-Villarreal, Oscar J.; Rossiter, John Anthony (Taylor & Francis, 2022)
Several solutions have been proposed in the literature to maximise the harvested ocean energy, but only a few consider the overall efficiency of the power take-off system. The fundamental problem of incorporating the power take-off system efficiency is that it leads to a nonlinear and non-convex optimal control problem. The main disadvantage of the available solutions is that none solve the optimal control problem in real-time. This paper presents a nonlinear model predictive control (NMPC) approach based on the real-time iteration (RTI) scheme to incorporate the power take-off system's efficiency when solving the optimal control problem at each time step in a control law aimed at maximising the energy extracted. The second contribution of this paper is the derivation of a condensing algorithm O(N2) for ‘output-only’ cost functions required to improve computational efficiency. Finally, the RTI-NMPC approach is tested using a scaled model of the Wavestar design, demonstrating the benefit of this new control formulation.
Keywords: Wave energy converters; nonlinear model predictive controller; real-time iteration; power take-off-system efficiency; condensing algorithm O(N2)